A COMPARATIVE STUDY OF ONDANSETRON WITH RAMOSETRON IN PREVENTION OF POST-OPERATIVE NAUSEA AND VOMITING IN PATIENTS UNDERGOING GENERAL ANESTHESIA - Ramakrishna Bandaru; Pramila T; Prathibha T; BV, surendra (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Post-operative nausea and vomiting (PONV) is an unpleasant, distressing, and exhausting experience for patients. PONV may prolong recovery, delay patient discharge, and increase hospital costs. Prevention and treatment of PONV help to accelerate post-operative recovery and increase patient satisfaction. In this study, we compared the efficacy of Ondansetron and Ramosetron to prevent PONV in patients undergoing elective surgeries under general anaesthesia and also to study their side effects. Methods: Eighty patients (American Society of Anesthesiologists [ASA] I and II) between the age group of 18 and 65 years scheduled to undergo elective surgeries under general anaesthesia were randomly allocated into two groups. Group O received Ondansetron 4 mg and Group R received Ramosetron 0.3 mg intravenously before induction of anaesthesia. Episodes of nausea, vomiting, and retching were determined and noted in first 24 h after surgery at time intervals of 0–3 h, 3–6 h, 6–12 h, and 12–24 h. The incidence of adverse effects and the use of rescue anti-emetics were also noted in the post-operative period. At the end of the surgery, results were compiled and statistical analysis was done using Student’s “t” test and Chi-square test. p<0.05 was considered as significant. Results: The incidence of nausea was lower in patients receiving Ramosetron when compared to patients receiving Ondansetron especially in the 0–3 h period (p=0.032). This was statistically significant. The incidence nausea was lower in Group R during 3–6 h, 6–12 h, and 12–24 h period which was not statistically significant (p=1.000, p=0.359, p=1.000 respectively). The incidence of vomiting was lower in patients receiving Ramosetron when compared to patients receiving Ondansetron in the 0–3 h, 3–6 h, 6–12 h, and 12–24 h period, but it was not statistically significant (p=0.712, p=1.000, p=0.241, and p=0.116, respectively). The use of rescue anti-emetics and the incidence of adverse side effects were more in patients receiving Ondansetron when compared to patients receiving Ramosetron with no significance. Conclusion: Our study concludes that ramosetron was more effective than ondansetron in the prevention of post-operative nausea and was associated with fewer side effects comparatively.